Pemaknaan Audiens terhadap Citra Perempuan Tangguh pada Konten Cinta Laura di Instagram dan YouTube - Laura Permata; Lusia Savitri Setyo Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The development of social media has created new ways for audiences to interpret the image of women, particularly through content presented by public figures. Cinta Laura, as a prominent public figure, consistently delivers inspirational content on Instagram and YouTube that represents strong women. This study aims to explore and describe how audiences interpret Cinta Laura's strong female image across these platforms. Drawing on Stuart Hall’s audience reception theory, concepts of representation, image, and digital communication, the study emphasizes the active role of audiences in constructing the meanings of media messages. A qualitative descriptive approach using a phenomenological method was employed to examine audiences’ subjective experiences and interpretations, with data collected through in-depth interviews with six followers of the Instagram account @claurakiehl and subscribers to the YouTube channel Puella. Findings indicate that audiences interpret Cinta Laura’s strong female image through three positions of meaning: dominant, negotiated, and oppositional readings. Audiences perceive Cinta Laura as intelligent, independent, and principled, while also adjusting these meanings in light of personal experiences and social contexts. Some content is considered overly idealistic, highlighting that interpretations of a strong female image are subjective, dynamic, and influenced by audience backgrounds. Perkembangan media sosial telah menciptakan cara baru bagi audiens untuk memahami citra perempuan, terutama melalui konten yang disajikan oleh figur publik. Cinta Laura, sebagai salah satu figur publik, secara konsisten menyajikan konten inspiratif di Instagram dan YouTube yang merepresentasikan perempuan tangguh. Penelitian ini bertujuan untuk mengeksplorasi dan mendeskripsikan bagaimana audiens menafsirkan citra perempuan tangguh yang ditampilkan oleh Cinta Laura melalui kedua platform tersebut. Mengacu pada teori audience reception Stuart Hall, konsep representasi, citra, dan komunikasi digital, penelitian ini menekankan peran aktif audiens dalam membentuk makna pesan media. Pendekatan kualitatif deskriptif dengan metode fenomenologi digunakan untuk menggali pengalaman dan pemaknaan subjektif audiens, dengan data yang dikumpulkan melalui wawancara mendalam terhadap enam pengikut Instagram @claurakiehl dan subscriber YouTube Puella. Hasil penelitian menunjukkan bahwa audiens menafsirkan citra perempuan tangguh Cinta Laura melalui tiga posisi pemaknaan, yakni dominant, negotiated, dan oppositional reading. Audiens melihat Cinta Laura sebagai sosok cerdas, mandiri, dan berprinsip, tetapi juga menyesuaikan makna tersebut dengan pengalaman pribadi dan konteks sosial masing-masing. Beberapa konten dianggap terlalu idealis, menegaskan bahwa pemaknaan citra perempuan tangguh bersifat subjektif, dinamis, dan dipengaruhi oleh latar belakang audiens.